Thermal and Mechanical Properties Enhancement of Cement Mortar using Phosphogypsum Waste: Experimental and Modeling Study - Ragab, Ehab M.; Awwad, Tarek M.; Becheikh, Nidhal (Engineering, Technology & Applied Science Research, 2024)
This research presents an in-depth investigation into the application of phosphogypsum (PG), a by-product of phosphate fertilizer plants and chemical industries, as a replacement material for cement in mortar, with a focus on enhancing its thermal and mechanical properties. The influence of PG as a partial replacement for cement on the compressive strength of mortar after 3, 7, and 28 days is investigated. Utilizing the Box-Behnken design within Response Surface Methodology, this study analyzed factors, such as sulfuric acid concentration, washing time, calcination temperature, and PG to cement ratio. Results indicate that optimal PG levels enhance mortar strength, particularly at 28 days, through sustained ettringite formation and microstructure optimization. Sulfuric acid concentration and calcination temperature were identified as the most significant elements influencing compressive strength, with the latter improving PG quality and reactivity. A PG to cement ratio up to 10% was found beneficial, while washing time had a negligible effect. The research highlights a critical synergy between the sulfuric acid concentration applied during the purification of PG and the calcination temperature. A significant improvement of 21% in compressive strength was achieved, underscoring the combined effect of chemical and thermal treatment on PG’s efficacy in mortar. The increased sulfuric acid concentration is presumed to purify the PG by removing impurities, thus improving its reactivity. Concurrently, calcination alters the PG’s crystalline structure and diminishes its organic composition. This interdependent optimization is instrumental in enhancing the structural integrity of PG-modified mortar. The potential for raw PG to be used as an insulating material is more pronounced at higher replacement rates (10%), while sulphuric acid treated PG (SCPG) and heat treated PG (HTPG) seem to be unable to provide a clear insulative advantage.